Tariff Rates, Offshoring and Productivity: Evidence from German and Austrian Firm-Level Data - Thorsten Hansen (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
This paper studies the impact of trade liberalization in terms of tariff cuts within the Eastern European enlargement on German and Austrian firm productivity. Unique matching of data from 1994 to 2003 suggests that tariff reductions raise parent firm productivity significantly. A ten percentage point decrease in tariff rates can lead to total factor productivity gains of up to 2 percent. The data allow distinction between three types of tariffs: output, intra-firm and input tariff rates. The size of the results strongly depends on the type of tariff and country analyzed.
urn:nbn:de:bvb:19-epub-13238-1
Keywords: 330; Zoll; Handelsliberalisierung; Wirkungsanalyse; Multinationales Unternehmen; Auslandsverlagerung; Produktivität; Deutschland; Österreich; EU-Mitgliedschaft; Handelsliberalisierung; EU-Mitgliedschaft